PROPOSED MARKETING STRATEGY FOR APOTEK MULYANI TO INCREASE SALES IN THE COMPETITIVE MARKET - Dwi Asih Kurniati; Satya Aditya Wibowo; Gallang Perdana Dalimunthe (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
With the increasing competition in the pharmaceutical retail industry, Apotek Mulyani as a Indonesia local pharmacy in Depok, faces the related issue of stagnation and declining sales due to the dynamic pharmacy retail industry. To overcome these problems, the pharmacy requires an effective marketing strategy. This study aims to determine an appropriate strategy by conducting internal (STP, marketing mix (7Ps), VRIO, and value chain) and external (PESTEL, Porter's Five Forces, customer, and competitor) analyses. A mixed-method approach was used in this study, involving questionnaires distributed to 74 respondents to gain customer preferences and interviews to obtain the internal perspectives. The SERVQUAL model and cluster analyses were used to identify gaps and pharmacy customer segments. The results of the study indicate that although Apotek Mulyani has several advantages, some improvements are still needed in the quality of service provided. For this reason, a marketing strategy through STP and marketing mix (7Ps) is proposed for Apotek Mulyani. The marketing strategy and implementation plan are focused on improving several aspects, including increasing promotional activities, expanding digital access, and improving the service experience for customers. Ultimately, these initiatives can increase sales growth and strengthen Apotek Mulyani's position in an increasingly competitive market.